Analisis Perbandingan Biaya dan Produktivitas Pekerjaan Balok Menggunakan Metode AHSP 2016 dan Metode Lapangan pada Rumah Susun BPK RI Kota Gorontalo - I Kadek Widiarta; Mohamad Yusuf Tuloli; Arfan Usman Sumaga (Transbahasa, 2025)
One of the main aspects in building construction projects that significantly impacts the cost and duration of the project is beam work. The large volume of this work contributes to the overall cost and time of the project. Therefore, improving labor productivity is crucial to optimize cost and time expenditure. The parameters analyzed in this study include productivity analysis and unit price analysis. The final results of this study show that the daily productivity rate for beam formwork work based on the Unit Price Analysis (AHSP) of the Ministry of Public Works Regulation No. 28 of 2016 is 2.943 m²/day. In contrast, the field method achieved a productivity rate of 3.727 m²/day, resulting in a 21.04% difference between productivity according to AHSP 2016 and field performance. The cost comparison for beam formwork work, derived from the Unit Price Analysis (AHSP) of the Ministry of Public Works Regulation No. 28 of 2016, indicates a cost of IDR 106,456.00 per m². Using the field method, the cost is IDR 81,391.60 per m², showing a cost difference of approximately 23.54% between AHSP 2016 and field costs. Factors causing differences in cost and productivity include work methods, job supervision, labor quantity, coefficients, and variations in material usage.